Colloidal Photonic Crystals for Biomedical Applications. Issue 5 (8th February 2021) - Liao, Junlong; Ye, Changqing; Agrawal, Prajwal; Gu, Zhongze; Zhang, Yu Shrike
Abstract : Colloidal photonic crystals (PCs) have attracted extensive interests because of their excellent optical properties and advantages such as ease in preparation, cost‐effectiveness, and versatility in functionalizations. After decades of development, numerous types of colloidal PCs are developed and found various applications in the field of biomedicine, including biosensors, microcarriers, drug delivery, cell research, and organs‐on‐chips, among others. Herein, the basic concepts and recent progress concerning the applications of the colloidal PCs in the biomedical field are provided. Initially, a brief introduction of the design and fabrication of colloidal PCs that are widely used in biomedicine is presented. Subsequently, the utilities of the colloidal PCs and their representative works in each application area are discussed in detail. Finally, a summary of challenges and perspectives is presented. Abstract : Herein, a brief introduction to the colloidal photonic crystals (PCs) and their fabrication methods, the applications of these colloidal PCs in biomedicine, and the challenges and perspectives are presented.